Bobby Flay : chapter one : iconic recipes and inspirations from a groundbreaking American chef - Flay, Bobby; Timberlake, Emily (Clarkson Potter/Publishers, 2024)
"Over 100 essential recipes from one of the world's most well-loved chefs--Bobby Flay, whose restaurants indelibly shaped the American food landscape. With three decades' worth of television appearances, restaurant openings, and game-changing recipes to his name, few chefs have touched so many Americans' lives with their cooking as Bobby Flay. In Bobby Flay Chapter One, Flay showcases 100 of his and his fans' favorite dishes, many of which have never been published, and assembles them into one striking, definitive volume. In poignant, heartfelt, and often hilarious stories, Flay looks back on his greatest culinary hits--and even laughs at some of his misses--giving readers an unprecedented look at his culinary inspirations and creative process. From big, bold Southwestern-influenced flavors like Blue Corn Pancakes Filled with Barbecue Duck, Shiitake, and Habanero Chile Sauce to contemporary twists on classic American favorites like Philly-Style Strip Steak with Provolone Cheese Sauce, Sautéed Mushrooms, and Shallots, Flay blended diverse influences into uniquely delicious creations throughout his career. With in-the-trenches stories from his groundbreaking restaurants like Mesa Grill, Bolo, and Gato, and recipes for his iconic dishes, Chapter One celebrates the first thirty years of Bobby Flay's culinary evolution. More than just a cookbook, this is a must-have keepsake for Flay's millions of fans. Engaging personal essays reveal which of Flay's Iron Chef dishes are his personal favorites, who his culinary mentors were, and which of his many restaurant concepts was his favorite (and why he may even break his cardinal rule and consider reopening it). With stunning photography and design, Bobby Flay Chapter One follows a culinary journey that celebrates innovation, flavor, and a chef who changed the way Americans cook and eat"--